2020
DOI: 10.1111/cge.13750
|View full text |Cite
|
Sign up to set email alerts
|

New insight into the role of substance P/neurokinin‐1 receptor system in breast cancer progression and its crosstalk with microRNAs

Abstract: The neuropeptide substance P (SP) triggers a variety of tumor-promoting signaling pathways through the activation of neurokinin-1receptor (NK1R), a class of neurokinin G protein-coupled receptors superfamily. Recent researches in our and other laboratories have shown the overexpression of both SP and NK1R in breast cancer (BC) patients. SP/NK1R signaling is strongly implicated in the pathogenesis of BC through affecting cell proliferation, migration, metastasis, angiogenesis, and resistance. Therefore, SP/NK1R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…Since REST is downregulated in breast cancer, this results in an increased intratumoral SP-level. Considering the antitumoral effects of SP at lower levels, it has been proposed that intact SP stimulates tumorigenesis, while its bioactive fragments resulting from enzymatic hydrolysis can suppress tumor growth (54,55). While capsaicin-sensitive afferents are a pivotal source of CGRP, expression of this vasoactive neuropeptide was also not significantly lower in desensitized animals.…”
Section: Discussionmentioning
confidence: 99%
“…Since REST is downregulated in breast cancer, this results in an increased intratumoral SP-level. Considering the antitumoral effects of SP at lower levels, it has been proposed that intact SP stimulates tumorigenesis, while its bioactive fragments resulting from enzymatic hydrolysis can suppress tumor growth (54,55). While capsaicin-sensitive afferents are a pivotal source of CGRP, expression of this vasoactive neuropeptide was also not significantly lower in desensitized animals.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have recently demonstrated that SP induces a series of signaling pathways through NK1R that mediate cellular excitability in several human tumor cells. It has important roles in forming and spreading various tumor cells via migration, angiogenesis, and metastasis [11][12][13][14][15][16]. is is important since the prevention of metastasis is a major goal in treating tumors.…”
Section: Introductionmentioning
confidence: 99%
“…SP plays roles in neurogenic inflammation, wound healing, pain transmission, and vasodilatation. By activating NK-1R, it can induce tumor-initiating intracellular responses in various cancers, including lung cancer [ 24 ], retinoblastoma [ 25 ], glioblastomas [ 26 ], breast cancer [ 27 ], and pancreatic cancer [ 28 ], and is correlated with cancer development and progression. The SP/NK-1R can substantially promote the activation of NF- κ B, which positively regulates transcription factors that favor tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%